AB0527 Comparison of Two Initial Prednisone Dose Regimens in Giant Cell Arteritis. (15th July 2016) - Sousa, A.; Martínez-Vidal, A.; Soto-Peleteiro, A.; Lorenzo, R.; Baroja, A.; Vázquez-Triñanes, C.; Argibay, A.; Freire, M.; Rivera, A.
Abstract : Background: Giant cell arteritis (GCA) is a vasculitis affecting large vessels and it is the most frequent type in patients over 50 years old. Although glucocorticoids (GC) still remain the mainstay of treatment in all these cases there is no yet clear evidence about optimal initial dose, regimen and relapses predictors and treatment [1, 2]. Objectives: To assess the characteristics of treatment, relapse and outcomes of a biopsy-proven GCA patients and to compare these items between groups based on initial oral prednisone dose. Methods: We performed a retrospective review of all patients diagnosed of biopsy-proven GCA in our institution (Complejo Hospitalario Universitario de Vigo) between 1 January 2000 and 31 December 2014. Additionally, they fullfilled at least 2 of other 4 1990 ACR classification criteria. Epidemiological, clinical and laboratory data, treatment and outcome of all these patients at diagnosis and during follow-up were analysed. We also compared groups by initial oral prednisone dose (≤40mg/day vs >40mg/day) using Cox models. Results: During study period 70 patients were identified and analysed. Mean age at diagnosis was 77±7 years old and fifty-one (73%) were female. Charlson index was ≤1 in 83% of cases. Most frequent presenting symptoms were headache (87%), polymyalgia rheumatica (57%) and jaw claudication (48.6%). Ischaemic manifestations at diagnosis were seen in ten patients (14.3%). Median ESR and CRP was 88±26mm/h [31–140] and 92±88mg/dL [4–326] respectively. Median delay time from first symptom until diagnosis was 2 months [0–72]. We also analysed patients divided in two groups based on initial oral predisone dose (≤40mg/day [17 patients] vs >40mg/day [53 patients]). No differences was seen in sex, age, comorbidities (including cardiovascular risk factors), antiagregants/ immunosupressive therapy use or laboratory markers. Nevertheless prednisone dose at first month (30.2mg/day vs 48.6mg/day; p=0.001), time to reach ≤5mg/day of prednisone (11.8 vs 16 months; p=0.045) and total prednisone dose (7.2 vs 11.5 grams; p=0.001) were significantly higher in >40mg/day group although we did not see more GC-related adverse effects in this group (p=0.38). During follow-up period (median 29 months [3–140]) 18 patients had at least one relapse, however we did not observe statiscal differences between both groups (18% in ≤40mg/day vs 28.8% in >40mg/day; p=0.35). Time to first relapse (12±11.3 months in ≤40 vs 16±12.9 months in >40; p=0.67) and total treatment time (28±23.5 in ≤40 vs 35±25.1 months in >40) were similar in boths groups. We could not identified any factor that was related to relapses in our multivariate analysis. Twenty-two patients died during follow-up period but none were related with GCA. Conclusions: High-dose prednisone was the most frequent initial treatment of GCA patients. Lower doses regimen could be as safe and effective as the high-dose regimen. Relapses were seen in ¼ of patients but we could not identified any factor associated with them. References: Salvarani C, Cantini F, Hunder GG. Polymyalgia rheumatica and giant-cell arteritis. Lancet 2008; 372: 234–45. Les I, Pijoan JI, Rodríguez-Άlvarez R et al. Effectiveness and safety of medium-dose prednisone in giant-cell arteritis: a retrospective cohort study of 103 patients. Clin Exp Rheumatol 2015; 33 (Suppl 89): S90–97. Disclosure of Interest: None declared